Reality Therapy as an Intervention for Smoking Behaviour: Evidence From Middle-Aged Individuals in Egbeda Local Government Area, Ibadan, Nigeria - Asiyanbi, Mutiat; Omopo, Oluwaseun Emmanuel; Umanhonlen, Sylvester Ehimare; Shoyemi, Adekunle Adeyinka (NIU Journal of Social Sciences; Vol 11 No 1 (2025): NIU Journal of Social Sciences, Vol. 11 No. 1, March 2025DO - 10.58709/niujss.v11i1.2080, 2025)
Smoking is a behaviour that afflicts many people, especially in this period of life when it poses greater health risks for middle-aged people. A lot of attempts have been made to quit smoking, yet many smokers continue to battle with it. Although addictions to behaviour such as smoking have found some efficacy with interventions like Reality Therapy, research has been scant on its efficacy in smoking cessation. This study seeks to determine the effects of Reality Therapy on reducing smoking behaviour among middle-aged individuals in Egbeda Local Government Area. The study was experimental in design, which included a pre-test and post-test. A total of 22 participants, 12 of who were in the Reality Therapy group and 10 in the control group, were recruited for this study. The age range was from 40 to 60 years. Participants in the Reality Therapy received a structured intervention. No treatment was given to the control group. Data from the participants were analysed using t-tests to compare pre-test and post-test smoking behaviour scores. The Reality Therapy group revealed significant reduction in smoking behaviour (mean difference = 6.1, t = 5.32, p = 0.000; while control group showed only a marginal reduction (mean difference 0.2), which was not statistically significant (t = 0.98, p = 0.330). The findings indicate that Reality Therapy is effective in reducing smoking behaviour among middle-aged men and women. Based on the findings, it is recommended that Reality Therapy be integrated into public health initiatives targeting smoking cessation, especially in middle-aged populations. Policymakers should also consider financing and supporting therapy-based intervention which inspires personal responsibility and informed choice in health behaviours. Long-term effects of Reality Therapy and its applicability across divides need to be examined. Keywords: Reality Therapy, smoking behaviour, middle-aged individuals, behavioural intervention